Adopting lean principle as sustainable manufacturing strategy in an electronic-enabled supply chain environment. (4th June 2010) - So, Stuart C.K.
This paper empirically examines the influence of lean supply strategy implemented in electronic-enabled manufacturing supply chains (EMSC) on lean manufacturing adoption in a sustainable manner. Adopting lean manufacturing often not only requires a lengthy period but also involves a prolonged decision process which makes sense to identify the antecedents for improving decision making. The influential factors including information sharing and use of e-business system in supplier integration together with lean performance-based supplier selection were tested with statistical methods based on survey data. It was found that lean manufacturing adoption is positively influenced by all these factors. Moreover, the results revealed that manufacturers may commit ongoing use of lean principle only if it has been adopted as regular practice. Lastly, managerial implications and future research were discussed to alleviate practical concerns in the execution of waste-reducing lean supply strategy and to explore the potential of developing reverse logistics on this platform.